Teachers' Innovation Strategies Based on Local Wisdom Through Strengthening Servant Leadership, Employee Engagement, Organizational Climate, and Learning Organizations - Sri Rohayati; Sri Setyaningsih; Lina Novita (International journal of technology and education research, 2025)
This study aims to examine teachers' innovation strategies based on local wisdom through strengthening servant leadership, employee engagement, organizational climate, and learning organizations. Educational innovation is an important aspect in improving the quality of learning, and local wisdom as the foundation of innovation strategies can provide a relevant and contextual approach. This study adopts a quantitative approach using surveys to collect data from teachers and staff in several schools. The main variables studied include servant leadership, employee engagement, organizational climate, and learning organization, which are linked to the implementation of innovation based on local wisdom. The results show that strengthening servant leadership and employee engagement plays a significant role in creating an organizational climate that supports sustainable learning. Additionally, strong learning organizations can facilitate the effective implementation of innovation. These findings have practical implications for the development of education policies that focus more on human resource empowerment and the integration of local values into learning practices.